Elimination of ochratoxin A from white and red wines: Critical characteristics of activated carbons and impact on wine quality. (April 2021) - Cosme, Fernanda; Inês, António; Silva, Davide; Filipe-Ribeiro, Luís; Abrunhosa, Luís; Nunes, Fernando M.
Abstract: Ochratoxin A (OTA) is a mycotoxin frequently found in wines, with an allowed maximum limit of 2.0 μg/L. To optimise OTA removal from white and red wines at high levels (10.0 μg/L) using activated carbons (ACs) different commercial deodorising ACs were tested. OTA elimination from white wines was less dependent on ACs characteristics, with 100% removal with all but one AC with the lowest total pore volume. For red wines, only one of the ACs with higher abundance of mesopores was successful in completely removing OTA. This decrease in performance was due to the competition of anthocyanins for ACs mesopores. ACs treatment impacted positively on white wine chromatic characteristics, decreasing the yellowness-brownish colour but for the red wine it was observed a higher but limited impact (maximum 24% decrease) on wine colour. ACs pore volume distribution, with pore sizes in the range 42.6–55.9 Å and 125.6–137.4 Å were important for efficient OTA removal. These results will allow the rational design of ACs with pore volume characteristics for OTA elimination with less impact on wine colour. Therefore, it was shown for the first time that AC with appropriate pore size distribution can remove completely OTA from white and also red wines. Highlights: Activated carbon (AC) can eliminate ochratoxin A (OTA) from white and red wines. Activated carbons characteristics are of utmost importance for red wine treatment. OTA removal was dependent on the mesopore volume of activated carbons. Anthocyanins levels in red wine cause a decrease in OTA removal efficiency. AC pore volume distribution impacts on OTA removal efficiency in red wines.